The Facilities and Infrastructure Readiness of Indonesian Shipping Company - Sholihah, Sita Aniisah; Afriliani, Desri; Bijaksana, Gena; Abdurachman, Edi; Ricardianto, Prasadja; Ferdiansyah, Anton (Institut Transportasi dan Logistik Trisakti, 2025)
A shipping company was assigned to deliver heavy cargo owned by electric steam power plant, PLTU SUMSEL-8. The company should prepare the necessary facilities and infrastructure to ensure a smooth delivery. The research purpose is to analyze the impact of facility and infrastructure readiness on the smooth transport of heavy cargo mediated by the supervision of the shipping company. The study used a Quantitative method with data collected through Likert-scale questionnaire distributed to a sample of 30 operational employees directly involved in the task. The data analysis was conducted using Path Analysis. The result shows a positive and significant influence of facility and infrastructure readiness on the supervision provided by the company. However, there is a less significant direct influence of the facilities and infrastructure readiness of the heavy cargo smooth transportation that could be interpreted as the possibility of other factors determine the smooth transportation apart from the facilities and infrastructure readiness.